Silica nanoparticles alleviate cadmium toxicity to Pisum sativum L. seedling growth by remodeling carbon-nitrogen metabolism - Yang, Xiaohuan; Zhao, Weifeng; Li, Hongxin; Sun, Lingling; Wang, Liyin; Wang, Ziran; Yang, Jingyi; Zhang, Baoqiong; Zhao, Liangyi; Zhang, Xibin; Sun, Liangliang; Ma, Jinhu (Frontiers in Plant Science, 2025)
The increasing incidence of soil cadmium (Cd) pollution significantly hinders the sustainable development of agriculture and food security. Improving crop stress resistance through nanobiotechnology represents a secure and sustainable approach for increasing the efficiency of treating soils contaminated with heavy metals. This study investigated the physiological and molecular mechanisms by which silica nanoparticles (nSiO2) alleviate plant Cd toxicity via ZW6 pea as the experimental material. These results indicate that Cd treatment severely impedes the growth and development of peas. However, nSiO2 application notably increased the lateral root number (25.00%), primary root length (33.93%), leaf dry weight (29.18%), root dry weight (17.41%), and photosynthesis rate (13.84%), thereby reducing the degree of oxidative damage caused by Cd toxicity. Moreover, Cd content in the roots (22.24%) and leaves (67.88%) of pea seedlings decreased with nSiO2 treatment, improving mineral nutrition and alleviating Cd-induced growth inhibition. Transcriptomic analysis revealed differentially expressed genes (DEGs) in pea seedlings subjected to Cd toxicity and nSiO2 treatment, revealing the molecular response of these plants to Cd stress. The addition of nSiO2 alongside Cd toxicity altered the C/N metabolic pathway in peas, particularly affecting sucrose and amino acid metabolism. This study highlights the effectiveness of nSiO2 in reducing Cd accumulation, mitigating oxidative stress, enhancing micronutrient absorption, restructuring metabolic pathways, and alleviating the growth inhibition caused by Cd toxicity. These findings provide a theoretical framework for enhancing crop stress resistance in agriculture through nanoparticle technology, offering a novel strategy for managing farmland contamination by heavy metals and promoting sustainable agricultural practices.